Bioinspired Ultrahigh Frequency Antenna for Partial Discharge Detection in High-Voltage Equipment - Ardila-Rey, Jorge Alfredo; Figueroa Karmelic, Daniel; Pizarro, Francisco; Govindarajan, Suganya; Albuquerque De Castro, Bruno [UNESP]; Schurch, Roger (Institute of Electrical and Electronics Engineers (IEEE), 2024)
The detection of partial discharges (PDs) is vital to evaluate the condition of the insulation systems in high-voltage equipment. Although various methods exist to measure the presence of PD, ultrahigh frequency (UHF) approaches have been widely adopted due to their ease of application and their ability to perform measurements without the need for direct galvanic contact with the equipment under test. One of the main challenges with these measurement methods is having sensors with adequate dimensions, bandwidth, and gain, to efficiently measure, in any environment, the electromagnetic (EM) emissions that propagate from the PD pulses even if they are of very low magnitude. This article presents the development of a new bioinspired antenna based on the structural characteristics of the antennae of the Antheraea Polyphemus moth. The bioinspired parameters of the proposed antenna were carefully adjusted to obtain a portable antenna (27.4× 14.4 cm), with an average gain of 3.07 dBi (between 1.36 and 4.45 dBi) and a bandwidth that covers the entire frequency spectrum, where the most important spectral power contents of PD are emitted (1750 MHz below -10 dB). The results obtained confirm that the proposed antenna is more sensitive than others, such as the Vivaldi antenna or the monopole antenna, commonly used in UHF PD measurements, since it allows accurate temporal and spectral differentiation of the PD pulses, even when the PD is of low magnitude.
Keywords: Bioinspired antenna; high-voltage equipment monitoring; partial discharges (PDs); ultrahigh frequency (UHF) detection